Diablerie : [compact disc, unabridged] : a novel - Mosley, Walter (Tandor Media Inc./Tandor Audio, 2008)
Ben Dibbuk has a good job, an accomplished wife, a bright college-age daughter, and a patient young mistress. Even as he goes through the motions of everyday life, however, inside he feels nothing. The explanation for this emotional void lies in the years he spent as a blacked-out drunk before pulling his life together--years in which he knows he committed acts he doesn't remember. Then a woman from his past turns up at a gala for his wife's new gig at a magazine called Diablerie and makes it clear that she remembers something he doesn't. Their encounter sets wheels in motion that will propel Dibbuk toward new knowledge, and perhaps the chance to feel again.--From amazon.com.